KUALITAS MINYAK KELAPA SAWIT DI PT. WANAPOTENSI GUNA MUSI BANYUASIN - Noriega, Nelissa (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2024)
This research is entitled Quality of palm oil at PT Wanapotensi Guna Musi Banyuasin. The formulation of the problem in this study is how the quality of water content, impurities and free fatty acids of CPO at PT Wanapotensi Guna? The aim is to determine the quality of water content, impurities and free fatty acids of CPO at PT Wanapotensi Guna. The research method is The method used in this research activity is by direct observation and literature review. The results showed that PT Wanapotensi Guna is an oil palm plantation that produces CPO through seven stages, namely harvesting oil palm fruits, sorting, boiling, separating, lubricating, pressing, and refining. Then, the CPO will be tested for quality based on three parameters, namely, moisture content, impurity content and free fatty acid content. CPO at PT Wanapotensi Guna, obtained an average value for free fatty acids (ALB) of 3.77%, moisture content of 0.12%, and dirt content of 0.19%, the value of the three still meets the SNI CPO quality standards.